PHARMACEUTICAL FORMS BASED ON PUNIC GRANATUM - Olimpia Dumitriu Buzia; Con Madalina; Earar Kamel; Dorel Firescu; Rebegea Laura; Alin Laurentiu Tatu (Romanian Society of Oral Rehabilitation, 2021)
The paper aimed to capitalize on the active principles and properties of Punica granatum extracts. An antibacterial product for external use was made using Punica granatum exocarp extract and a food supplement for internal use, with Punica granatum mesocarp extract, rich in substances with antioxidant properties. We obtained an extractive solution of Punica granatum, from exocarp, and another from mesocarp. We performed the quantitative and qualitative analysis of the two extracts, we determined qualitatively and quantitatively the content of polyphenols, flavonoids, using the spectrophotometric method. I dosed vitamin C, a powerful antioxidant, by titration with Tillman reagent. We obtained two pharmaceutical forms, respectively, a syrup and a soap, having as active principle the extract of punica granatum or in other words, pomegranate.